A myocutaneous flap variation for management of distal hindlimb wounds in the cat - Dermisiadou, E; Panopoulos, I; Psalla, D; Georgiou, S; Sideri, A; Galatos, A; Flouraki, E; Tsioli, V (Journal of the Hellenic Veterinary Medical Society, 2025)
Management of complex feline hindlimb defects is challenging. However, the use of a split semitendinosus myocutaneous (SST) flap for coverage has not yet been reported. The objective of this study was to describe the SST flap and compare it with second-intention healing for the management of complex tibial defects in cats. Two wounds were created on each tibia of 12 purpose-bred laboratory DSH cats. Wounds in group A (n=12) were covered with SST flaps and those in group B (n=12) were left to heal by second intention. In both groups, clinical assessment scoring and planimetry were performed between 1 and 30 postoperative days. CT angiography (CTA) and histological examination were performed on days 0, 10, and 30 and on days 0, 14, 6, and 12 months postoperatively, respectively. Group A had significantly higher assessment scores on days 7 (p=0.002), 14 (p<0.001), 21 (p=0.001), and 30 (p=0.008). The time to complete healing in group A (32,42 days) was significantly higher than that to complete epithelial coverage in group B (24.67 days) (p=0.001). On CTA, significant differences were observed in ST muscle density which was higher on day 10 compared to 0 on the proximal (dP) (p<0.001) and medial (dM) points (p=0,020, p<0,001, p<0,001 respectively) in all three different phases. For the distal (dD) point, the measurement was significantly higher in the precontrast phase (p=0.001) and on day 10 compared today 30 atn all points in all three phases (p<0.001). The caliber of the distal caudal femoral artery and vein and of the proximal gluteal artery and vein were significantly higher on day 10 than on day 0 (p<0.001), on days 10 to 30 (p<0.001), and on days 30 to 0 (p=0.004, p=0.006, p=0.011, p=0.007, respectively). Histologically significant differences were observed on inflammation and muscle cell degeneration which were higher on day 14 than on day 0 and 6 months (p<0.001, p<0.001, p<0.001, p=0.007 respectively). Neovascularization and fibrosis were significantly higher on day 14 than on day 0 (p=0.010 and p=0.009, respectively). In conclusion, although the ST muscle can be safely longitudinally split and cover tibial defects, the SST flap is less efficient than second-intention healing in terms of the time to complete wound healing.